Factors explaining the shortage and poor retention of qualified health workers in rural and remote areas of the Kayes, region of Mali: a qualitative study - Mohamed Ag Ahmed; Soumaïla Diakité Koman Sissoko; Marie- Gagnon; Sylvie Charron (James Cook University, 2020)
Introduction: Shortage of health workers is a worldwide problem but is particularly critical in sub-Saharan Africa. In Mali, the number of health workers is insufficient and their retention is low, particularly in rural and remote areas. Rural postings are unattractive to health workers. Very few studies have examined the factors contributing to the shortage and poor retention of health workers in Mali. The objective of this study is to identify and understand these factors with regards to skilled health workers in two rural health districts (Yélimané and Bafoulabé) in the region of Kayes, Mali. Methods: This qualitative study is based on the conceptual framework of Lehman, Dieleman and Martineau. Data were collected through 46 in-depth interviews with health workers and decision-makers. A thematic content analysis was conducted with the support of QDA Miner software. Results: The study identified factors contributing to the insufficient allocation and poor retention of rural health workers in these districts. They are individual-level factors (gender, family situation, age), unattractive living and working conditions, community recognition and participation, quality of leadership, an unfavourable recruitment/assignment process and insufficient financial incentives. It shows that female staff have specific constraints that prevent them from deploying to or staying in rural areas for long periods. In addition, the number of staff recruited at the national level is unpredictable and insufficient, while their recruitment and assignment process is perceived to be inequitable and not very transparent, disadvantaging rural health structures. Some strategies were identified to improve the availability and retention of health workers in these areas. They take into account certain social norms, notably gender roles, and include the improvement of living and working conditions, as well as the strengthening of health workforce management. Conclusion: This study's findings highlight the multifaceted nature of factors contributing to the availability and retention of health workers in rural and remote areas of sub-Saharan Africa and the challenges associated with them. This study identifies some strategies that can be combined to facilitate the retention and availability of health workers in these areas. Some strategies involve actors outside the health sector, requiring joint efforts for their implementation. This research provides decision-makers with evidence to support informed decision making with regards to the retention of health workers in rural areas.